Policies, procedures and risk aversity: police decision-making in domestic violence matters in an Australian jurisdiction. (26th November 2021) - Meyer, Silke; Reeves, Ellen
ABSTRACT: Domestic violence (DV) is an issue of global concern, which has been subject to public health and criminal justice reforms for decades. Much attention has been paid to legal responses to DV, specifically the policing of this social issue. Police responses have frequently been scrutinised for not taking DV seriously, not placing sufficient emphasis on perpetrator accountability and not recognising and acknowledging victim survivor preferences sufficiently. The current study examines police responses to DV in an Australian jurisdiction that has been subject to substantial DV-focused policy and law reforms in recent years. Drawing on focus group data from 19 police officers and prosecutors, this article examines the factors that shape police decision making when responding to DV. Findings identify a shift towards more proactive and protective policing of DV, guided by a strong emphasis on operational policies and procedures, risk perceptions and aversity. Findings further reveal limited room for victim preferences in police responses to DV, highlighting the need for specialist DV units to provide holistic and nuanced responses to families affected by DV.